Experimental and quantum chemical evaluation of dihydropyridine derivative as environmental benign corrosion inhibitor for mild steel in 15% HCL - Ansari K.R.; Quraishi M.A. (My University, 2025)
The behavior of 1,1’-{2, 6-dimethyl-4-[-2-phenylethenyl]-1,4-dihydropyridine-3,5-diyl}diethanone (DHP) have been investigated as mild steel (MS) corrosion inhibitor in 15% HCl solution by gravimetric measurements, electrochemical impedance spectroscopy (EIS), potentiodynamic polarization (Tafel), scanning electron microscopy (SEM) analysis. Quantum chemical calculation was applied to correlate electronic structure parameters with the inhibition performances. Adsorption of DHP obeys the Langmuir’s isotherm. Potentiodynamic polarization measurements showed that DHP acted as mixed type inhibitor but cathodically dominant. © 2015 by CEE (Center of Excellence in Electrochemistry).